Tinjauan Sistematis Terhadap Implementasi Rekam Medis Elektronik Pada Pelayanan Rawat Jalan - Diastri, Anggraina; Kurniawan, Rico (Politeknik Negeri Jember, 2025)
The implementation of Electronic Medical Records (EMR) in Indonesia presents a strategic opportunity to improve the quality and efficiency of healthcare services by optimizing access to medical information and strengthening coordination among healthcare professionals. However, its implementation still faces major challenges, particularly in terms of data security and workforce readiness. This study aimed to evaluate the benefits, challenges, and impacts of EMR adoption on medical practice and healthcare delivery. The research was conducted using a systematic literature review method with a PRISMA approach. A total of 4,475 articles were identified from four major databases: PubMed, Google Scholar, ScienceDirect, and Scopus. After screening titles, abstracts, and full texts, 10 articles met the inclusion criteria and were further analyzed. The findings indicated that EMR can accelerate access to patient information, enhance coordination among medical teams, and reduce the risk of documentation errors. This review suggests that EMR has significant potential to improve the efficiency, accuracy, and quality of outpatient services. However, the success of its implementation largely depends on technical readiness, human resource capacity, and infrastructure support. Further efforts should focus on improving digital literacy among healthcare workers, strengthening data security, and developing infrastructure to support the optimal implementation of EMR systems.